MENELUSURI KAIDAH HUKUM MAKANAN HALAL DALAM PERSPEKTIF AL QUR’AN SURAT AL MAIDAH AYAT 4 - Ilmiah, Novi Bahrotul; Humaidah, Lusiana Nur (Islamic Banking & Economic Law Studies (I-BEST), 2024)
Surah Al-Maidah Verse 4 in the Al-Quran talks about the rules of halal food from a religious perspective This verse states that food that is good and according to taste is permitted to be eaten, as long as there are no religious guidelines that prohibit it. In this study, the author discusses the concept of halal food from the perspective of Al Maidah verse 4. The author conducted research using the library research method by combining appropriate verses. In this research, the author tries to explain the meaning of halal with verse 4 of the Qur'an surah al Maidah